2001
DOI: 10.1111/j.1574-6941.2001.tb00873.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biotransformation of fuel oxygenates under sulfate-reducing conditions

Abstract: The anaerobic biotransformation of methyl tert‐butyl ether (MTBE), ethyl tert‐butyl ether (ETBE), and methyl tert‐amyl ether (TAME) was evaluated under different anoxic electron‐accepting conditions. Enrichments were established with a polluted estuarine sediment inoculum under conditions promoting denitrification, sulfate reduction, Fe(III) reduction, or methanogenesis. Complete loss of MTBE and TAME was observed under sulfate‐reducing conditions, concomitant with the reduction of sulfate. A stoichiometric am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 16 publications
2
34
0
2
Order By: Relevance
“…One previous study by Somsamak et al (2001) reported complete loss of MTBE in sulfate enrichment incubations with fuel contaminated estuary sediment. In their study, 1.1 mM MTBE was transformed to a stoichiometric amount of TBA with the concomitant reduction of sulfate after 1,160 days of incubation.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…One previous study by Somsamak et al (2001) reported complete loss of MTBE in sulfate enrichment incubations with fuel contaminated estuary sediment. In their study, 1.1 mM MTBE was transformed to a stoichiometric amount of TBA with the concomitant reduction of sulfate after 1,160 days of incubation.…”
Section: Discussionmentioning
confidence: 96%
“…Methane has not been detected at any point with this enrichment; therefore clone analysis with Archaeal primers was not performed. Sulfate has been widely reported as a significant electron acceptor for in situ, anaerobic MTBE and TBA transformation (Bradley et al 2001a(Bradley et al , b, 2002Somsamak et al 2001). Therefore, culture NW2 will be critical to understanding …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations